Compulsory Religious Education: A Justification Based on European Experience - Koukounaras-Liagkis, M. (Ireland International Conference on Education, 2012 Proceedings, Infonomics Society, 2012)
In this paper the author presents research into the role of religion in the modern world and into young people’s perspectives on the role of religion in European school systems attempting to justify compulsory Religious Education. International and European legislation, experiences of different countries and findings of researches in Greece published for the first time, provide a proposal for compulsory Religious Education which has to be based on the constructivist theory according to pedagogical practice in Europe.